2013
DOI: 10.1002/jbmr.2166
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Arg-Gly-Asp Sequence/Integrin α5β1-Mediated Signal Involvement in Embryonic Enchondral Ossification by Exo Utero Development System

Abstract: Enchondral ossification is a fundamental mechanism for longitudinal bone growth during vertebrate development. In vitro studies suggested that functional blockade with RGD peptides or with an antibody that interferes with integrin a5b1-ligand interactions inhibited pre-hypertrophic chondrocyte differentiation. The purpose of this study is to elucidate in vivo the roles of the integrin a5b1-mediated signal through the Arg-Gly-Asp (RGD) sequence in the cell-extracellular matrix (ECM) interaction in embryonic enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…We previously reported that a5b1 integrin plays a critical role in ANGPTL2 function in several tissues 11e13 , analyses that did not include chondrocytes. A previous report by others indicated anomalous chondrocyte differentiation and endochondral ossification in long bones of mice in which a5b1 integrin signaling had been blocked, phenotypes similar to those reported here in Angptl2 knockout mice 29,30 . In addition, p38 MAPK signaling is part of a major pathway governing bone development and remodeling 9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that a5b1 integrin plays a critical role in ANGPTL2 function in several tissues 11e13 , analyses that did not include chondrocytes. A previous report by others indicated anomalous chondrocyte differentiation and endochondral ossification in long bones of mice in which a5b1 integrin signaling had been blocked, phenotypes similar to those reported here in Angptl2 knockout mice 29,30 . In addition, p38 MAPK signaling is part of a major pathway governing bone development and remodeling 9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, mice in which cartilage-specific β1-integrin is conditionally knocked out exhibited dyschondroplasia similar to that of LPA 1 KO mice 33 . Furthermore, topical administration of anti-α5β1-integrin antibody or RGD-containing peptide to the upper limbs of mouse fetuses suppressed chondrocyte proliferation and shortened the upper limbs 34 . Together, these findings indicate that β1-integrin and LPA 1 have closely related roles in the formation of cartilage.…”
Section: Discussionmentioning
confidence: 97%
“…Studies using isolated chick sternal chondrocytes found that blocking α1, α2, or β1 integrins reduced survival and hypertrophic differentiation ( Hirsch et al, 1997 ) while studies in mouse limb organ culture using antibodies to α5β1 found that this integrin also plays a role in chondrocyte differentiation and joint formation ( Garciadiego-Cazares et al, 2004 ). Similar ex vivo experiments used injections into the upper limbs of mouse embryos of antibodies to α5β1 or RGDS peptides to support a role for the α5β1 integrin in endochondral ossification ( Inoue et al, 2014 ).…”
Section: Integrin–matrix Interactions In Cartilagementioning
confidence: 99%